Skin Viral Infections: Host Antiviral Innate Immunity and Viral Immune Evasion - Lei, Vivian; Petty, Amy J.; Atwater, Amber R.; Wolfe, Sarah A.; MacLeod, Amanda S. (Frontiers in Immunology, 2020)
The skin is an active immune organ that functions as the first and largest site of defense to the outside environment. Serving as the primary interface between host and pathogen, the skin’s early immune responses to viral invaders often determine the course and severity of infection. We review the current literature pertaining to the mechanisms of cutaneous viral invasion for classical skin-tropic, oncogenic, and vector-borne skin viruses. We discuss the skin’s evolved mechanisms for innate immune viral defense against these invading pathogens, as well as unique strategies utilized by the viruses to escape immune detection. We additionally explore the roles that demographic and environmental factors, such as age, biological sex, and the cutaneous microbiome, play in altering the host immune response to viral threats.